2008
DOI: 10.1002/pssb.200880272
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of auxetic phenomena in nanoporomaterials

Abstract: Porous materials are efficient structures in respect to optimizing strength and stiffness for a given weight. A new means of improving the characteristics of the samples may be realized using abnormal deformation properties of auxetic porous materials having a negative Poisson's ratio ν. Auxetic porous materials are suitable for creating adaptive contact joints and for replacing damaged biotissue. It is known that the inverted or re‐entrant cell structure of porous auxetics may be obtained by isotropic permane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The prediction model showed that the nanoporomaterials have good strength and deformation performance. 45 Auxetic polymeric materials cooperated with other properties will give a big leap in application.…”
Section: Auxetic Polymersmentioning
confidence: 99%
“…The prediction model showed that the nanoporomaterials have good strength and deformation performance. 45 Auxetic polymeric materials cooperated with other properties will give a big leap in application.…”
Section: Auxetic Polymersmentioning
confidence: 99%
“…Recently, more studies have been developed. The uniaxial compressive properties [17], dynamic properties [18,19], tension fatigue [20] and shape memory behaviours [21,22] of auxetic foams were studied by Scarpa et al The auxetic phenomena were predicted by Shilko et al [23] through investigating the deformation behaviours of porous materials under various types of loading. The mass-transport property was another potential application of auxetic foams [15], and Wojciechowski and co-workers [24] simulated fluid flow in a channel by finiteelement analysis (FEA).…”
mentioning
confidence: 99%